Hydrocarbon migration and accumulation in the Lower Cambrian to Neoproterozoic reservoirs in the Micangshan tectonic zone, China: New evidence of fluid inclusions - Tao Tian; Peng Yang; Zhanli Ren; Deliang Fu; Shixin Zhou; Fu Yang; Jing Li (Energy Reports, 2020)
The Lower Paleozoic reservoir in the Micangshan tectonic zone is a new shale gas exploration area with excellent potential. However, the hydrocarbon migration and accumulation histories of this reservoir have not been thoroughly elucidated and urgently require further research. Fluid inclusions offer a unique and useful method to test for hydrocarbon migration, accumulation, composition and timing. This study integrated the hydrocarbon charge history using fluid inclusions in the Lower Cambrian to Neoproterozoic reservoir from the Micangshan tectonic zone. This work involves the delineation and analysis of fluid inclusions using the petrography, spectroscopy and microthermometry of fluid inclusions. Based on the fluid inclusion analyses combined with reservoir thermal history, timing estimates and charge models of the hydrocarbons were obtained. The formation of natural gas was multifactorial in the Lower Cambrian to Neoproterozoic petroleum system, and the gas in the Niutitang (n) and Dengying (d) reservoirs was mainly from oil cracking and dry gas, and gas in the Xiannvdong (x) and Canglangpu (c) reservoirs was abiogenic and formed in hydrothermal fluids by regional tectonothermal events. Three well-defined stages of hydrocarbon charge were identified in the petroleum system in the Micangshan tectonic zone. The stage of oil charge first began before the Early Permian (277 Ma); the stage of gas charge from oil cracking occurred in the Late Triassic to Early Jurassic (212 Ma-198 Ma); and the stage of gas charge from dry gas occurred in the Middle Jurassic (173 Ma-166 Ma). The gas of mixed origin from the Niutitang reservoir was stored in the nanoscale pores as a self-reservoir, rather than as an effective gas source for the overlying reservoirs.
Keywords: 330; Fluid inclusion; Hydrocarbon charge history; Petroleum systems; Niutitang Formation; Micangshan tectonic zone